Nutritional counselling interactions between health workers and caregivers of children under two years: observations at selected child welfare clinics in Ghana - Nsiah-Asamoah, Christiana (BMC Health Serv Res, 2019)
BACKGROUND: This study evaluated the Health Works (HWs) nutritional counselling skills and information shared with caregivers. This was a cross-sectional study in which an observation checklist was used to examine Growth Monitoring and Promotion (GMP) activities and educational/counselling activities undertaken by health workers (HWs) to communicate nutrition information to caregivers, depending on the ages of the children. METHODS: A total number of 528 counselling interactions between health workers and caregivers in 16 Child welfare Clinics (CWCs) in two rural districts in Ghana were observed. Frequencies were presented for the information that was obtained from each caregiver and those that were provided by the HWs during the nutritional counselling sessions. RESULTS: About 95.1 and 61.8% of the caregiver-HW interactions involved mothers of children who were less than 6 months of age and those above 6 months respectively. HWs counselled the caregivers on appropriate nutrition for the child. Health talk messages that were shared with caregivers focused mainly on the importance of attending CWCs and vaccination of children and rarely included any teaching materials. In most of the interactions, HWs made of child’s feeding practices the past 1 month; and also did not provide advice on specific issues of IYCF. Nutritional counselling information given for non-breastfeeding children was inadequate and in some cases absent. Little attention was given to the feeding of children with animal products during counselling. CONCLUSION: Generally nutritional information given to caregivers who had children above 6 months was inadequate.